AIR PDAM DAN AIR SULINGAN DALAM KONSUMSI AIR DI KOTASURAKARTA - Kusdiyanto, Kusdiyanto; Riyardi, Agung (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
The objectives of this research are to analize factors that influence households demand for water from PDAM Kota Surakarta and to analize relationship between water from PDAM Kota Surakarta with distillate water. Employing double-log linier multiple regression it was found that households demand for water from PDAM Kota Surakarta was influenced by the price of water from PDAM Kota Surakarta, the price of distillate water, the households income and number of households family members. Also it was found that the relationship between water from PDAM Kota Surakarta with distillate water is substitution. The positive cross price elasticity indicated the substitution. The households income elasticity, the dominance of households income and the positive relation between number of households family members and households demand for water from PDAM Kota Surakarta, however, indicated the complementary relationship between water from PDAM with distillate water.